Exploring the impact of European Union Law on Energy and Environmental Taxation - Pirlot, A (Edward Elgar Publishing, 2020)
In this chapter, Alice Pirlot explores whether and how EU law has shaped the use of environmental tax measures – including environmental taxes and environmentally driven taxes and tax incentives – in the EU, drawing on existing literature on the topic. The author shows that EU law has shaped and continues to shape the development of environmental tax measures both at the level of the EU and at the level of the Member States. It is argued that at EU level, the institutional framework has not really helped in the enactment of environmentally driven taxes. The analysis of the historical development of EU provisions surrounding energy taxation illustrates this point. So far, the energy taxation directive remains largely disconnected from the EU’s climate policy, including the EU Emissions Trading Scheme. Second, EU substantive law has had an ambiguous impact on Member States’ environmental tax policy. On the one hand, EU substantive law has been interpreted by the Court of Justice in a way that encourages Member States to adopt tax measures that are environmentally driven. Indeed, the environmental purpose of Member States’ tax measures seems to play a positive role in the assessment of their compatibility with EU law, including State aid provisions, the fundamental freedoms and the energy taxation directive. On the other hand, in some instances, EU law strictly limits Member States’ ability to adopt environmentally driven tax measures. Moreover, it is shown that EU secondary law disregards the purpose of environmental taxes in order to classify them for statistical purposes.